Fluid Preloading Versus Ephedrine in the Management of Spinal Anesthesia-Induced Hypotension in patients undergoing Cesarean Delivery - Asad Khan, Maqsood Ahmed Siddiqui, Hira Asad, Shahid Hussain, Muhammad Taqi, Kelash Kumar (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To compare the efficacy of prophylactic ephedrine versus fluid preload (Hartmann’s solution) in preventing hypotension in women undergoing cesarean section under spinal anesthesia at a teaching hospital Methodology: Study was conducted in the Department of Anesthesiology at Liaquat University Hospital, Hyderabad from January 2023 to September 2023. Patients were randomly divided into two groups (Group A and Group B) using a draw method, where they selected sealed envelopes marked A or B. Group A received prophylactic ephedrine (0.25 mg/kg intravenous infusion immediately after bupivacaine injection), while Group B received prophylactic fluid preload (20 mL/kg Hartmann’s solution over 10–15 minutes before spinal anesthesia). Results: The study enrolled a total of 62 patients, equally divided into Group A and Group B, with 31 patients in each group. The two groups were comparable in terms of age (32.32 ± 5.62 years in Group A vs. 30.35 ± 3.31 years in Group B, p = 0.197) and BMI (26.96 ± 2.88 kg/m² in Group A vs. 27.03 ± 3.31 kg/m² in Group B, p = 0.964). In terms of efficacy, Group A demonstrated a significantly higher success rate compared to Group B (67.7% vs. 38.7%, p = 0.022). Conclusion: The frequency of hypotension is lower in women receiving prophylactic ephedrine during spinal anesthesia for cesarean section compared to those given a Hartmann’s solution preload. Keywords: Spinal anesthesia, Fluid preload, Hypotension, Ephedrine, Cesarean section.